Characterization of a minimal pKW2124 replicon from Weissella cibaria KLC140 and its application for the construction of the Weissella expression vector pKUCm1 - Ku, Hye-Jin; Park, Myeong Soo; Lee, Ju-Hoon (Frontiers in Microbiology, 2015)
A 2.1-kb plasmid was previously isolated from Weissella cibaria KLC140 in kimchi and cloned into pUC19 along with the slpA and gfp genes, resulting in an 8.6-kb pKWCSLGFP construct for use as a novel surface display vector. To reduce the size of the vector, the minimal replicon of pKW2124 was determined. The pKW2124 plasmid contains a putative origin of replication (ori), a potential ribosomal binding site (RBS), and the repA gene encoding a plasmid replication protein. To conduct the minimal replicon experiment, three different PCR products (MR1, ori + RBS + repA; MR2, RBS + repA; MR2’, repA; MR3, fragment of repA) were obtained and cloned into pUC19 (pKUCm1, pKUCm2, and pKUCm3, respectively) containing the chloramphenicol acetyltransferase (CAT) gene. These three constructed vectors were electroporated into W. confusa ATCC 10881 with different transformation efficiencies of 1.5×105 CFU/μg, 1.3×101 CFU/μg, and no transformation, respectively, suggesting that the putative ori, RBS, and repA gene are essential for optimum plasmid replication. Subsequent segregational plasmid stability testing of pKUCm1 and pKUCm2 showed that the vector pKUCm1 is highly stable up to 100 generations but pKUCm2 was completely lost after 60 generations, suggesting that the putative ori may be important for plasmid stability in the host strain. In addition, a host range test of pKUCm1 revealed that it has a broad host range spectrum including Weissella, Lactococcus, Leuconostoc, and even Lactobacillus. To verify the application of pKUCm1, the β-galactosidase gene and its promoter region from W. cibaria KSD1 were cloned in the vector, resulting in pKUGal. Expression of the β-galactosidase gene was confirmed using blue-white screening after IPTG induction. The small and stable pKUGal vector will be useful for gene transfer, expression, and manipulation in the Weissella genome and in other lactic acid bacteria.